Letter from Arnold O. Beckman to potential Beckman@Science conference attendees - Beckman, Arnold O. (1999)
This letter from Arnold O. Beckman invites potential attendees (and potential donors) to a conference on the future of science education in Orange County, California. This initiative to improve science education was titled Beckman@Science and was operational from 1998-1999.
Keywords: Science--Study and teaching; California--Orange County; Humanitarianism; Public schools; Education